(untitled) (University Park, Pennsylvania, 1994)
Since its first publication in 1992, New Perspectives on Historical Writing has become a key reference work used by students and researchers interested in the most important developments in the methodology and practice of history. For this new edition, the book has been thoroughly revised and updated and includes an entirely new chapter on environmental history. Peter Burke is joined here by a distinguished group of internationally renowned historians, including Robert Darnton, Ivan Gaskell, Richard Grove, Giovanni Levi, Roy Porter, Gwyn Prins, Joan Scott, Jim Sharpe, Richard Tuck, and Henk Wesseling. The contributions examine a wide range of interdisciplinary areas of historical research, including women's history, history "from below," the history of reading, oral history, the history of the body, microhistory, the history of events, the history of images, and political history.
Keywords: Historiography